The Variational Iteration Method for an Inverse Problem of Finding a Source Parameter (Advances in Applied Mathematics and Mechanics, 2018)
An inverse problem of determining unknown source parameter in a parabolicequation is considered. The variational iteration method (VIM) is presented to solveinverse problems. The solution gives good approximations by VIM. A numerical exampleshows that the VIM works effectively for an inverse problem.